A family for Gracie [large type] - Lillard, Amy (Lillard, Amy. Pontotoc Mississippi series, 2020)
"Gracie Glick is known for being the helpful one, always available for a relative in need. But now that she's longing for a home and family of her own, it's time to help herself. With few eligible men in Pontotoc, Gracie's choices, and her time, are limited. So she takes a bold leap of faith- she proposes to Matthew Byler, a handsome, recently widowed, father of five. It's not until after they're married that Gracie learns Matthew doesn't want more children ... With his grief still fresh, and his children needing care while he tends to his farm, Gracie is the answer to Matthew's prayers. But a marriage in name only suits him fine. And when he finally tells Gracie the dismaying reason why, they must decide whether to continue together-or apart"--